Floral Odors Can Interfere With the Foraging Behavior of Parasitoids Searching for Hosts - Desurmont, Gaylord A.; von Arx, Martin; Turlings, Ted C. J.; Schiestl, Florian P. (Frontiers in Ecology and Evolution, 2020)
Plants produce distinct blends of volatile compounds that attract pollinators (floral odors) or natural enemies of insect herbivores (herbivore-induced plant volatiles). The admixture of these blends in the atmosphere may alter the attraction of these mutualists and ultimately affect plant fitness. Here, using synthetic blends of Brassica rapa floral volatiles and real B. rapa flowers, we investigated how floral odors impact the foraging behavior of parasitoids. In an olfactometer setting, floral odors reduced the attractiveness of plants infested by herbivores to parasitoids by 43.5% and affected four out of five parasitoid species tested. Additionally, experiments with the parasitoid Cotesia glomerata revealed that the effects of floral odors are dose-dependent and that floral odors were less disruptive under wind tunnel conditions than under olfactometer conditions. Electroantennogram recordings showed that C. glomerata antennae do respond to floral compounds, but that floral compounds do not inhibit antennal responses to herbivore-induced leaf volatiles. In conclusion, floral odors can act as background pollutants decreasing the attractiveness of chemical blends used by natural enemies to locate their hosts. Under natural conditions, such interferences could affect the outcome of tritrophic interactions and may play an important role in the evolution of plant volatile signaling.